2009
DOI: 10.1210/jc.2008-1422
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Osteocalcin and Markers of Metabolic Phenotype

Abstract: Serum osteocalcin concentration was inversely associated with blood markers of dysmetabolic phenotype and measures of adiposity. Our findings should be considered hypothesis generating, and they need to be replicated in human studies designed to test the hypothesis that osteocalcin affects metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
257
6
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(310 citation statements)
references
References 33 publications
39
257
6
8
Order By: Relevance
“…Posterior crosssectional analysis involving 380 adults aged 65 years or more found a negative correlation between metabolic parameters and osteocalcin levels (26). In this report, 198 patients were followed for three years and those with high basal levels of osteocalcin had lower increase in plasma glucose during the follow -up (26).…”
Section: Osteocalcin Levels and Metabolic Parameters In Humansmentioning
confidence: 65%
See 1 more Smart Citation
“…Posterior crosssectional analysis involving 380 adults aged 65 years or more found a negative correlation between metabolic parameters and osteocalcin levels (26). In this report, 198 patients were followed for three years and those with high basal levels of osteocalcin had lower increase in plasma glucose during the follow -up (26).…”
Section: Osteocalcin Levels and Metabolic Parameters In Humansmentioning
confidence: 65%
“…Posterior crosssectional analysis involving 380 adults aged 65 years or more found a negative correlation between metabolic parameters and osteocalcin levels (26). In this report, 198 patients were followed for three years and those with high basal levels of osteocalcin had lower increase in plasma glucose during the follow -up (26). These results were later corroborated by a large cohort study that evaluated more than 2,760 elderly men and found lower levels of osteocalcin in the presence of metabolic syndrome, as well as worse glycemic and insulin sensitivity indexes (27).…”
Section: Osteocalcin Levels and Metabolic Parameters In Humansmentioning
confidence: 94%
“…(13) In another study conducted in older healthy men, serum osteocalcin concentrations were inversely associated with blood markers of dysmetabolic phenotype and measures of adiposity. (14) Such studies and others like them (15)(16)(17)(18)(19) suggest that that our proposed endocrine loop comprising insulin, the osteoblast, and osteocalcin represents a conserved regulatory pathway that participates in the global control of glucose metabolism in all bony vertebrates, including humans.…”
Section: From Mice To Humansmentioning
confidence: 76%
“…(17,19) Unfortunately, in this study, uncarboxylated OC, which is specifically reported to have hormonal activity, and blood glucose measurements were unavailable. Polymorphisms may not be able to reflect the status of posttranslational modification (g-carboxylation) that appears to be the mechanism by which OC bioactivity is regulated.…”
Section: Discussionmentioning
confidence: 97%
“…A cross-sectional study in elderly Swedish men reported inverse correlations between total OC and fat mass, (17) whereas a post hoc analysis of elderly male participants in a clinical trial reported similar inverse correlations with blood markers of dysmetabolic phenotype and measures of adiposity. (19) Another study in a Chinese population reported association between serum OC and lipid metabolism. (20) Despite the body of evidence for the role of OC in skeletal biology and energy metabolism, there are at present no studies that have evaluated associations between osteocalcin polymorphisms and measures of adiposity or body composition.…”
Section: Introductionmentioning
confidence: 99%